Echocardiographic Measures of Diastolic Function Are Preload Dependent during Triggered Positive Pressure Ventilation: A Controlled Crossover Study in Healthy Subjects - Peter Juhl-Olsen; Christian Alcaraz Frederiksen; Johan Fridolf Hermansen; Carl-Johan Jakobsen; Erik Sloth (Critical Care Research and Practice)
Background. The use of echocardiography in intensive care settings impacts decision making. A prerequisite for the use of echocardiography is relative resistance to changes in volume status and levels of positive pressure ventilation (PPV). Studies on indices of diastolic function report conflicting results with regard to dependence on volume status. Evidence is scarce on PPV. Methods. Ten healthy subjects were exposed to 6 levels of positive end-expiratory pressure (PEEP) and pressure support (PS) following a baseline reading. All ventilator settings were performed at three positions: horizontal, reverse-Trendelenburg, and Trendelenburg. Echocardiography was performed throughout. Results. During spontaneous breathing, early diastolic transmitral velocity () changed with positioning (), whereas early diastolic velocity of the mitral annulus () was independent (). With PPV, and proved preload dependent (). Increases in PEEP, PS, or a combination influenced and in reverse-Trendelenburg- and horizontal positions, but not in the Trendelenburg position. Discussion. The change towards preload dependency of with PPV suggests that PPV increases myocardial preload sensitivity. The susceptibility of and to preload changes during PPV discourages their use in settings of volume shifts or during changes in ventilator settings. Conclusion. Positioning and PPV affect and .